FAKTOR RISIKO KEJADIAN ABORTUS DI RSUD DR. CHASAN BOESOIRIE TERNATE PROVINSI MALUKU UTARA - Hubaya, Sitti; Arifin, M; Burhanuddin, Burhanuddin (UPPM Politeknik Kesehatan Kemenkes Ternate, Maluku Utara, Indonesia, 2015)
Abstract : This study aims to determine the risks of pregnancy outside marriage, contraception failure, socioeconomic status, history of abortion, and parity on the incidence of abortion in Hospital Dr.Chasan Boesoirie Ternate. The study design was a